The study of Sarawak women non government organizations (NGO's) towards empowering rural development/ Ain Fadilla Abdillah & Arina Zawiah Dollah - Abdillah, Ain Fadilla; Dollah, Arina Zawiah (2014)
This chapter focuses the background of study which is on the study of Sarawak Women Non Governmental Organisations (NGOs) towards empowering rural development. Section 1.1 discuses the background of the study, 1.2 explains on the problem statement and section 1.3 states the research objectives and 1.4 is research question. Section 1.5 is on the information regarding the scope of the study and section 1.6 explains the significant of study and lastly section 1.7 is all about definition of terms and concepts